Expectancy Theory in a Budgetary Setting: A Comment. - Dillard, Jesse F.; Jiambalvo, James (The Accounting Review, 1979)
This comment has pointed out differences between Rockness' model and his discussion of the model. We reformulated his model to account for alternative effort levels and pointed out the difference between behavioral choice models and job effort models. We hope future reseach efforts will be attentive to the nuances of the expectancy theory literature. We also indicated that two hypotheses, developed to test the descriptive validity of the model, do not follow from the model or from previous research in expectancy theory. In combination with the experimental design problems, this fact severely limits any conclusions regarding the model's descriptive validity.